Perancangan User Experience Aplikasi Online Market berbasis Mobile di Masa Pandemi menggunakan Metode Design Thinking - Carly Vyoletta Siagian; Ratih Kartika Dewi; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
In economic life, the market is something that has a very vital role. The market has a role as a place to shop for the daily needs of people's lives. However, starting in December 2019, where the Corona Virus appeared, there was a very fast spread of COVID-19 all over the world. As a result, people find it difficult to leave their homes to shop for their daily needs. Fears of being exposed to COVID-19 have made most people no longer shop for their daily needs directly at traditional markets. Due to this pandemic, people find it difficult to travel outside their homes so they tend to shop online. However, when shopping for needs online, of course there are still problems that are felt by the people. The perceived problems include the length of delivery time that is considered long, the products provided are not as numerous or varied as those on the market, there is a minimal nominal purchase, and cannot see the product directly. Based on the problems described previously, this research will design the user experience of the Online Market application to the high-fidelity prototype using the design thinking method. In the final stage, testing the high-fidelity prototype that has been designed using the usability testing method is carried out by involving 5 potential users. From the results of the testing stage, the design of this application solution got a score for the effectiveness aspect of 100%, the efficiency aspect got a score of 0.035 goals/second, and for the satisfaction aspect it got a SUS score of 88. Based on the SUS score, the Mapper application solution design got a B value, the word property rating is in the very good category, and is in the Acceptable category.